POLA RELASI PENCAMBUK-PENANGKIS DALAM TARIAN CACI DAN SUMBANGANNYA PADA ELEGANSI DIALOG DI INDONESIA - Sailtus, Fransiskus; Pandor, Pius (UI Scholars Hub, 2024)
This paper aims to explore the intersubjective relationship between the whipper (paki) and the parrier (ta’ang) in caci, a traditional dance from Manggarai, East Nusa Tenggara Province. For that purpose, this study applied the phenomenological method. In this method, caci is described based on what actually transpires during the performance when the researchers made direct observations. As a native Manggarai, the researcher has watched the dance for many years. Data from the phenomenological study were analyzed using Armada Riyanto’s philosophical concept of intersubjective relationality. This study found that the relationship between the whipper and the parrier in caci is not a subject-object but intersubjective one. The intersubjectivity of the whipper-parrier relationship is demonstrated by several facts. First, there is subjective identity of the whipper and parrier in the form of their names. Second, there is affirmation of identity and its confirmation during the dance. Third, the act of whipping and parrying does not involve a large group of people, but only the whipper and parrier as individual actors. Fourth, the whipper and parrier are aware of the other party’s presence and role. Fifth, the whipper is aware of the presence and role of the parrier and vice versa. Sixth, the whipper and parrier are encountering each other with mutual respect. The intersubjective element of the whipper-parrier relationship is highly relevant to the promotion of elegant intercultural dialogues in Indonesia.